2001
DOI: 10.1086/319190
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Trophic Cascades: How Much Do They Trickle?

Abstract: Although more consensus is now emerging on the magnitude and frequency of cascading trophic effects in aquatic communities, the debate over their terrestrial counterparts continues. We used meta-analysis to analyze field experiments on trophic cascades in terrestrial arthropod-dominated food webs to evaluate the overall magnitude of trophic cascades and conditions affecting their occurrence and strength. We found extensive support for the presence of trophic cascades in terrestrial communities. In the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
275
4
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(303 citation statements)
references
References 111 publications
22
275
4
2
Order By: Relevance
“…When all predators of herbivores (avian, mammalian, invertebrate) are taken into consideration, meta-analyses of terrestrial tritrophic cascades have shown that predatorexclusion beneWts herbivorous arthropods more than harms plants (Halaj and Wise 2001;Mooney et al 2010), but that vertebrate carnivores usually have a stronger impact than invertebrate predators (Schmitz et al 2000). Moreover, previous reviews of terrestrial trophic cascades have often used a large variety of predators where the speciWc eVects of one predator group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When all predators of herbivores (avian, mammalian, invertebrate) are taken into consideration, meta-analyses of terrestrial tritrophic cascades have shown that predatorexclusion beneWts herbivorous arthropods more than harms plants (Halaj and Wise 2001;Mooney et al 2010), but that vertebrate carnivores usually have a stronger impact than invertebrate predators (Schmitz et al 2000). Moreover, previous reviews of terrestrial trophic cascades have often used a large variety of predators where the speciWc eVects of one predator group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Huusela-Veistola (1998) also found that perennial grass strips enhance spider populations in the strip and the adjacent field, which is similar to the findings of Bayram and Luff (1993) and Jmhasly and Nentwig (1995). Bayram and Luff (1993) emphasize the role of grassy perennial strips as an overwintering site for spiders, and Halaj and Wise (2001) showed in a meta-analysis that in the majority of experiments, predator removal led to increased levels of herbivorous insects and higher levels of plant damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of ants as terrestrial top predators and the effects of predators on plant damage and biomass have been previously reviewed through meta-analyses of trophic cascades (Halaj and Wise 2001;Schmitz et al 2000), to the best of our knowledge, a deeper and specific meta-analysis of the protective role of ants on plants has yet to be done. Therefore, we aimed to use meta-analytical methods to: (1) determine the magnitude of the effect of ant presence on herbivory rates and parameters of plant fitness, (2) investigate whether there are differences in the magnitude of those effects in tropical versus temperate regions, (3) compare the magnitude of the effects of removal of single versus several ant species, (4) compare the magnitude of the effects in relationship to different ant attractors, attractor combination and number as well as attractor position on the plant, and (5) compare the magnitude of effects on obligate ant-plants (=myrmecophytes) and facultative (=myrmecophile) relationships between ants and host plants, in both tropical and temperate regions.…”
Section: Introductionmentioning
confidence: 99%